2004
DOI: 10.3171/jns.2004.101.4.0633
|View full text |Cite
|
Sign up to set email alerts
|

Acute alterations in microvascular basal lamina after subarachnoid hemorrhage

Abstract: Results of this study demonstrated an acute loss of collagen IV from the cerebral microvasculature after SAH and indicated that MMP-9 contributes to this event. The loss of collagen IV might contribute to the known failure of the blood-brain barrier after SAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
81
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(89 citation statements)
references
References 63 publications
8
81
0
Order By: Relevance
“…SAH causes profound reductions in cerebral blood flow (CBF), reduced cerebral autoregulation, and acute cerebral ischemia. [122][123][124][125][126] These pathophysiological processes are linked to raised intracranial pressure and decreased cerebral perfusion pressure, 122,127,128 decreased availability of nitric oxide, 126,129 acute vasoconstriction 123,130,131 and microvascular platelet aggregation, 132 activation of microvascular collagenases, loss of microvascular collagen, 133 and endothelial barrier antigen leading to decreased microvascular perfusion and increased permeability. 132,133 Despite recent advances in the understanding of the mechanisms of SAH-induced brain injury, few effective treatments exist, and further research is needed.…”
Section: Prevention Of Sahmentioning
confidence: 99%
“…SAH causes profound reductions in cerebral blood flow (CBF), reduced cerebral autoregulation, and acute cerebral ischemia. [122][123][124][125][126] These pathophysiological processes are linked to raised intracranial pressure and decreased cerebral perfusion pressure, 122,127,128 decreased availability of nitric oxide, 126,129 acute vasoconstriction 123,130,131 and microvascular platelet aggregation, 132 activation of microvascular collagenases, loss of microvascular collagen, 133 and endothelial barrier antigen leading to decreased microvascular perfusion and increased permeability. 132,133 Despite recent advances in the understanding of the mechanisms of SAH-induced brain injury, few effective treatments exist, and further research is needed.…”
Section: Prevention Of Sahmentioning
confidence: 99%
“…Inoue [39] and Inoue and Kisilevski [40] reported abundant microfibril-like β-amyloid in the basement membrane in the cerebrovascular amyloid angiopathy of Alzheimer's disease. Sehba et al [75] demonstrated an acute loss of collagen IV from the cerebral microvasculature after aneurysmal subarachnoid haemorrhage.…”
Section: Introductionmentioning
confidence: 99%
“…7,11,22,23,28 MMP-9 levels in CSF and peripheral blood were significantly increased in patients with SAH. 11,22 MMP-9 degrades the extracellular matrix proteins of cerebral microvessel basal lamina and interendothelial tight junction proteins such as ZO-1, causing BBB disruption and brain edema formation.…”
Section: Discussionmentioning
confidence: 97%
“…11,22 MMP-9 degrades the extracellular matrix proteins of cerebral microvessel basal lamina and interendothelial tight junction proteins such as ZO-1, causing BBB disruption and brain edema formation. 23,28 A recent study showed that MMP-9 knockout inhibited post-SAH brain edema formation in mice. 7 Inflammatory cytokines and other factors can regulate the transcription of MMP-9 following SAH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation